2005
DOI: 10.1086/502538
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of the Source (Patient Versus Staff) on Nosocomial Norovirus Outbreak Severity

Abstract: Patient-indexed norovirus outbreaks generally affect more patients than do staff-indexed outbreaks. Staff appear to be similarly affected by both outbreak index category groups. This study demonstrates the importance of obtaining complete outbreak data, including the index case classification as staff or patient, during norovirus outbreak investigations. Such information may be useful for further targeting prevention measures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 26 publications
0
17
0
2
Order By: Relevance
“…The norovirus outbreak at our long-term care facility is an example of how workers continue to work with symptoms of a contagious disease. Although we cannot directly link transmission from staff to residents due to limitations in data collection, there are many case reports that implicate ill health care workers as vectors for transmission of diseases such as influenza10, pertussis11, methicillin-resistant Staphyloccous aureus 12, and norovirus 13,14. Norovirus is of particular concern with regards to presenteeism.…”
Section: Discussionmentioning
confidence: 99%
“…The norovirus outbreak at our long-term care facility is an example of how workers continue to work with symptoms of a contagious disease. Although we cannot directly link transmission from staff to residents due to limitations in data collection, there are many case reports that implicate ill health care workers as vectors for transmission of diseases such as influenza10, pertussis11, methicillin-resistant Staphyloccous aureus 12, and norovirus 13,14. Norovirus is of particular concern with regards to presenteeism.…”
Section: Discussionmentioning
confidence: 99%
“…In one review of reported nosocomial outbreaks, researchers estimated that more cases are involved in outbreaks tied to patient index cases than in staff-originated outbreaks and that patientindexed outbreaks require more aggressive hygiene interventions in order to disrupt viral transmission (144).…”
Section: Health Care Settingsmentioning
confidence: 99%
“…We did not identify any member of staff as a probable source for norovirus infection among hospitalized patients; the primary case among the staff occurred on December 3, 2006, and the primary case among hospital-patients occurred on versus December 1, 2006. Mattner et al recently categorized published nosocomial norovirus outbreaks into those triggered by patients and those triggered by staff: in general, more patients are affected in index-patient outbreaks than in index-staff outbreaks; staff appear to be similarly affected by both categories of outbreak index group [15].…”
Section: Discussionmentioning
confidence: 99%